POLA PERILAKU MASYARAKAT DALAM PENGURANGAN RESIKO BENCANA TANAH LONGSOR DI KECAMATAN BANJARWANGU KABUPATEN BANJARNEGARA JAWA TENGAH - juhadi, juhadi; Kurniasari, Nia (Universitas Negeri Semarang, 2016)
Objective of this research to determine the pattern of behavior of the community in disaster risk reductionlandslide in the Banjarmangusub district of Banjarnegara district. The main research method is survey.Data collection technique used test, questionnaire, observation, documentation, interviews and Focus GroupDiscussion (FGD). Quantitative and qualitative approaches are used in the data analysis of this research.The results showed a pattern of behavior in the research community did not show any significant correlationwith the knowledge and attitudes the community in efforts to reduce the risk of landslides. Attitudes andknowledge of the community in disaster risk reduction landslides goodenough, but not yet reflected in thepattern of behavior. The pattern of behavior of local communities in efforts to reduce the risk of landslidesstill low.